Internet of Things based Electric Vehicle Security and Tracking - R, Barathvaj P; A, Gokul; P, Kaamesh P; R, Harirajan; S, Jaswanth; Suja, S. (Journal of ISMAC, 2023)
The aim of this research is to introduce a security system that utilizes IoT and GPS tracking technologies to provide enhanced safety measures. Cayenne and GSM technologies are employed in the proposed system to provide real-time tracking and security features. The system comprises of GPS unit, microcontroller, GSM unit, and Cayenne dashboard. The GPS module is used to obtain the location of the device, while the microcontroller processes the data and sends it to the Cayenne dashboard through the internet. The GSM module is used for real-time communication with the device and to send an alert upon occurrence of any security breaches. The Cayenne dashboard provides an easy-to-use interface for monitoring and controlling the device remotely. The proposed system provides an effective and reliable solution for tracking and securing women and children, especially in potentially dangerous situations. The system can be easily implemented and customized to suit various tracking and security requirements.